Polyethylene / aramid fiber composite fiber asphalt mixture as well as preparation method and application thereof
By using the crude aggregate layered pre-mix method to re-dollar ultra-high molecular weight polyethylene fiber and aramid fiber in the asphalt mixture, the aramid fiber agglomeration problem is solved, significantly improving the high-temperature performance, fatigue characteristics and anti-aging and cracking characteristics of the asphalt mixture, and extending the service life of the asphalt pavement.
Patent Information
- Application Number
- CN202411811425.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, aramid fibers are prone to agglomeration in asphalt mixtures, resulting in insufficient mechanical enhancement effects, and insufficient high-temperature performance, fatigue characteristics and anti-aging and cracking characteristics.
The crude aggregate layered premix method is used to blend ultra-high molecular weight polyethylene fibers and aramid fibers into the asphalt mixture, and the polyethylene fibers are dissolved through hot asphalt to reduce the electrostatic phenomenon of aramid fibers. The dispersion of aramid fibers is enhanced through the dispersion space and friction between the aggregates to form a stable three-dimensional network structure.
It significantly improves the dispersion of aramid fiber in asphalt mixture, improves its high temperature stability, fatigue resistance and anti-aging and cracking characteristics, thereby extending the service life of asphalt pavement.
Smart Images

Figure CN119638272A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of road engineering, and specifically relates to a polyethylene / aramid composite fiber asphalt mixture and a preparation method and application thereof. Background Art
[0002] As vehicle loads and road traffic increase, cracks will gradually appear in the asphalt layer of the road, and rutting damage and fatigue cracks will occur on the asphalt pavement, which will affect the service life of the asphalt pavement and increase the cost of road maintenance and repair. An effective way to improve the performance of asphalt mixtures is to add fibers. Fibers can effectively control and slow down the expansion of cracks caused by temperature changes and loads. After cracks initiate, fibers can play a bridging role, thereby delaying the expansion and development of cracks. Fibers form a three-dimensional reinforcement network structure in asphalt mixtures, improve their compressive strength and shear strength, and enhance the stability and bearing capacity of the overall structure.
[0003] At present, the types of fibers used in asphalt mixtures mainly include natural fibers, mineral fibers and synthetic fibers. Compared with other fibers, synthetic fibers have higher tensile strength and toughness, which significantly improves the crack resistance and fatigue resistance of asphalt mixtures. They can also maintain good stability under high temperature conditions, thereby reducing the deformation of asphalt mixtures under high temperature conditions. In addition, synthetic fibers have higher UV resistance and aging resistance, and are not easy to degrade during the long-term service of asphalt pavements.
[0004] Aramid fiber is a synthetic fiber based on aromatic polyamide. It has been widely used in composite materials, aerospace engineering and thermal protection fields because of its excellent properties such as light weight, high strength, high temperature resistance and corrosion resistance. The strength and toughness of aramid fiber are significantly higher than those of steel wire, and its density is lower, which provides the advantage of light weight. In addition, its thermal decomposition temperature exceeds 450°C, showing extremely high thermal stability. The addition of aramid fiber to asphalt mixture helps to significantly improve the mechanical properties of asphalt mixture and effectively extend its fatigue life. However, aramid fiber is a bundle fiber. During the addition and mixing process, aramid fiber is prone to agglomeration in asphalt mixture, thereby affecting the mechanical properties of aramid fiber asphalt mixture. At present, there is still a lack of an applicable mixing method to evenly add aramid fiber to asphalt mixture and fully and efficiently enhance the mechanical reinforcement effect of aramid fiber in asphalt mixture. Summary of the invention
[0005] The purpose of the present invention is to provide a polyethylene / aramid composite fiber asphalt mixture and its preparation method and application, so as to overcome the shortcomings of the prior art, improve the dispersibility of aramid fiber in the asphalt mixture, solve the problem of agglomeration of aramid fiber in the asphalt mixture and improve the high temperature performance, fatigue characteristics and anti-aging cracking characteristics of the asphalt mixture.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In the first aspect, the present invention provides a polyethylene / aramid composite fiber asphalt mixture, the raw material composition of which is as follows by weight percentage: 5.8%-6.0% asphalt, 0.05%-0.1% polyethylene / aramid fiber, 40%-59% coarse aggregate, 36%-53% fine aggregate and 5%-7% mineral powder.
[0008] In some other embodiments, the polyethylene / aramid composite fiber asphalt mixture is an asphalt concrete mixture with a nominal maximum particle size of 9.5 mm-19 mm.
[0009] In some other embodiments, the lengths of the polyethylene fiber and the aramid fiber are both 15-20 mm, and the mixing mass ratio of the polyethylene fiber to the aramid fiber is (1-5):1;
[0010] Preferably, the lengths of the polyethylene fiber and the aramid fiber are both 19 mm, and the mixing mass ratio of the polyethylene fiber to the aramid fiber is 4:1.
[0011] In some other embodiments, the coarse aggregate is crushed stone with a particle size of 3-20 mm, and the fine aggregate is crushed stone with a particle size of 0.075-3 mm.
[0012] In some other embodiments, the mineral powder is limestone mineral powder and slag powder.
[0013] Or, the asphalt is base asphalt;
[0014] Or, the polyethylene fiber is an ultra-high molecular weight polyethylene fiber, and the molecular weight of the polyethylene fiber is 3-4 million;
[0015] Or, the aramid fiber is Kevlar aramid fiber.
[0016] In a second aspect, the present invention provides a method for preparing the polyethylene / aramid composite fiber asphalt mixture according to the first aspect, comprising the following steps:
[0017] (1) Preheat the coarse aggregate, fine aggregate, asphalt and mixing tools separately;
[0018] (2) First, mix the coarse aggregate with aramid fiber, then add asphalt and polyethylene fiber, and finally add fine aggregate and mineral powder.
[0019] The principle of the technical solution of the present invention is as follows: ultra-high molecular weight polyethylene fiber and aramid fiber are mixed into asphalt mixture by the layered premixing method of coarse aggregate. During the mixing process, the ultra-high molecular weight polyethylene fiber dissolves in the hot asphalt, reducing the static electricity phenomenon of the aramid fiber. There is sufficient dispersion space between the coarse aggregates, which is conducive to the dispersion of the ultra-high molecular weight polyethylene fiber and the aramid fiber during the mixing process. The friction between the aggregates improves the dispersion of the aramid fiber, which is more conducive to the formation of a three-dimensional network stable structure of the fiber. The ultra-high molecular weight polyethylene fiber has a high stabilizing effect when dissolved in asphalt, and the aramid fiber has a high mechanical strength. The asphalt mixture prepared by this process has high high temperature stability, fatigue resistance and anti-aging cracking characteristics.
[0020] In some other embodiments, in step (1), the preheating temperature of the coarse aggregate and the fine aggregate is 160-170°C for 20-30 hours; the preheating temperature of the asphalt is 150-155°C for 1-2 hours; the preheating temperature of the mixing tool is 150-155°C for 1-2 hours;
[0021] Preferably, the preheating temperature of the coarse aggregate and the fine aggregate is 165°C for 24 hours;
[0022] The asphalt is preheated at 155°C for 2 hours;
[0023] The mixing tool is preheated to 155°C for 2 hours.
[0024] In some other embodiments, in step (2), the mixing process is: dividing the aramid fiber and the preheated coarse aggregate into multiple portions, taking one portion of the coarse aggregate and mixing it with one portion of the aramid fiber to obtain a first mixture; taking another portion of the coarse aggregate and adding it to the first mixture, adding the remaining aramid fiber and mixing it to obtain a second mixture; adding the remaining coarse aggregate to the second mixture, mixing it, adding asphalt and polyethylene fiber and mixing it, and finally adding fine aggregate and mineral powder and mixing it;
[0025] Preferably, the aramid fiber is divided into 2 equal parts, and the preheated coarse aggregate is divided into 3 parts; first, 1 / 3 of the coarse aggregate is mixed with 1 / 2 of the aramid fiber to obtain a first mixture; then 1 / 3 of the coarse aggregate is added to the first mixture and mixed, and the remaining 1 / 2 of the aramid fiber is added to mix to obtain a second mixture; the remaining 1 / 3 of the coarse aggregate is added to the second mixture and mixed, asphalt and polyethylene fiber are added to mix, and finally fine aggregate and mineral powder are added to mix.
[0026] In some other embodiments, in step (2), the mixing time of the asphalt and the polyethylene fiber is 180-200 seconds;
[0027] The mixing time of the fine aggregate and the mineral powder is 100-120s;
[0028] Preferably, the mixing time of the asphalt and the polyethylene fiber is 180s;
[0029] The mixing time of the fine aggregate and mineral powder is 120s.
[0030] In a third aspect, the present invention provides use of the polyethylene / aramid composite fiber asphalt mixture described in the first aspect in asphalt road construction.
[0031] Beneficial effects of the present invention:
[0032] Polyethylene / aramid fiber composite asphalt mixture is a higher strength pavement material that can be used to pave safer and more economical asphalt pavements. When designing asphalt pavement structures, the thickness of polyethylene / aramid fiber composite asphalt mixture can be reduced, saving pavement material resources. In addition, under the same thickness as traditional asphalt pavement, the service life of polyethylene / aramid fiber composite asphalt pavement can be greatly extended, thereby reducing the maintenance and resurfacing costs during the design life of the asphalt pavement. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0034] Figure 1 This is the polyethylene / aramid fiber composite asphalt mixture mixing method used in the embodiment of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with specific embodiments of the present invention to provide a detailed and complete description of the technical solutions therein. It should be noted that these embodiments only represent a part of the present invention, rather than all possible embodiments.
[0036] Example 1
[0037] A method for preparing a polyethylene / aramid composite fiber asphalt mixture comprises the following steps:
[0038] Step 1, weigh ultra-high molecular weight polyethylene fiber (molecular weight of 3.5 million), aramid fiber (Kevlar aramid fiber developed by DuPont, USA) and asphalt for use, prepare coarse aggregate, fine aggregate and mineral powder according to the grading type. The grading type is shown in Table 1. It can be seen from Table 1 that, taking SUP 19 and SUP 9.5 as examples, the contents of coarse aggregate, fine aggregate and mineral powder are determined by the passing rate of the grading type.
[0039] Among them, the asphalt (PG64-22 matrix asphalt) content of the asphalt mixture is 6.0wt.%, the mass of polyethylene / aramid fiber accounts for 0.05% of the mass of the asphalt mixture, the mass ratio of ultra-high molecular weight polyethylene fiber and Kevlar aramid fiber is 4:1, the length of ultra-high molecular weight polyethylene fiber and Kevlar aramid fiber are both 19mm, and the nominal maximum particle size of the asphalt mixture is 9.5mm.
[0040] Table 1 Grading types
[0041]
[0042] Step 2: Preheat the coarse aggregate, fine aggregate and mineral powder in an oven at 165°C for 24 hours; preheat the asphalt and mixing tools in an oven at 155°C for 2 hours.
[0043] Step 3, adding Kevlar aramid fiber into the preheated aggregate, mixing the aggregate and Kevlar aramid fiber for 60 seconds, adding asphalt and ultra-high molecular weight polyethylene fiber into the mixing pot, and stirring for another 240 seconds.
[0044] Example 2
[0045] This Example 2 is based on the steps of Example 1, with the difference that first, fine aggregate and mineral powder are added to the mixing pot, then Kevlar aramid fiber is added, asphalt and ultra-high molecular weight polyethylene fiber are added and stirred for 60 seconds, and finally coarse aggregate is added and stirred for 240 seconds. The other steps are consistent with Example 1.
[0046] Example 3
[0047] This Example 3 is based on the steps of Example 1, with the difference that coarse aggregate is first added to the mixing pot, then Kevlar aramid fiber is added, asphalt and ultra-high molecular weight polyethylene fiber are added and stirred for 60 seconds, and finally fine aggregate and mineral powder are added and stirred for 240 seconds. The other steps are consistent with Example 1.
[0048] Example 4
[0049] This embodiment 4 is based on the steps of embodiment 1, except that all the aggregates are evenly divided into three parts, 1 / 3 of the aggregates are added to the mixing pot, and 1 / 2 of the Kevlar aramid fiber is added. Then 1 / 3 of the aggregates are added to the mixing pot, and then 1 / 2 of the Kevlar aramid fiber is added, and then 1 / 3 of the aggregates are added to the mixing pot. Finally, asphalt and ultra-high molecular weight polyethylene fiber are added and stirred for 300 seconds. The other steps are consistent with embodiment 1.
[0050] Example 5
[0051] This embodiment 5 is based on the steps of embodiment 1, except that the aggregate is divided into coarse aggregate, fine aggregate and mineral powder, and then the coarse aggregate is evenly divided into three parts, 1 / 3 of the coarse aggregate is added to the mixing pot, and 1 / 2 of the Kevlar aramid fiber is added. Then 1 / 3 of the coarse aggregate is added to the mixing pot, and then 1 / 2 of the Kevlar aramid fiber is added, and then 1 / 3 of the coarse aggregate is added to the mixing pot, asphalt and ultra-high molecular weight polyethylene fiber are added and stirred for 180 seconds, and finally fine aggregate and mineral powder are added and stirred for 120 seconds. The other steps are consistent with embodiment 1.
[0052] Example 6
[0053] A method for preparing a polyethylene / aramid composite fiber asphalt mixture comprises the following steps:
[0054] Step 1, weigh ultra-high molecular weight polyethylene fiber, Kevlar aramid fiber and asphalt for use, prepare coarse aggregate, fine aggregate and mineral powder according to the gradation type, and the gradation type is shown in Table 1.
[0055] Among them, the asphalt content of the asphalt mixture is 5.8wt.%, the mass of polyethylene / aramid fiber accounts for 0.05% of the mass of the asphalt mixture, the ratio of ultra-high molecular weight polyethylene fiber to Kevlar aramid fiber is 4:1, the length of ultra-high molecular weight polyethylene fiber and Kevlar aramid fiber are both 19mm, and the nominal maximum particle size of the asphalt mixture is 19mm.
[0056] Step 2: Preheat the coarse aggregate, fine aggregate and mineral powder in an oven at 165°C for 24 hours; preheat the asphalt and mixing tools in an oven at 155°C for 2 hours.
[0057] Step 3, adding Kevlar aramid fiber into the preheated aggregate, mixing the aggregate and Kevlar aramid fiber for 60 seconds, adding asphalt and ultra-high molecular weight polyethylene fiber into the mixing pot, and stirring for another 240 seconds.
[0058] Example 7
[0059] This embodiment 7 is based on the steps of embodiment 6, except that the aggregate is divided into coarse aggregate, fine aggregate and mineral powder, and then the coarse aggregate is evenly divided into three parts, 1 / 3 of the coarse aggregate is added to the mixing pot, and 1 / 2 of the Kevlar aramid fiber is added. Then 1 / 3 of the coarse aggregate is added to the mixing pot, and then 1 / 2 of the Kevlar aramid fiber is added, and then 1 / 3 of the coarse aggregate is added to the mixing pot, asphalt and ultra-high molecular weight polyethylene fiber are added and stirred for 180 seconds, and finally fine aggregate and mineral powder are added and stirred for 120 seconds. The other steps are consistent with embodiment 6.
[0060] Comparative Example 1
[0061] A common hot-mix asphalt mixture, which consists of 3-10mm coarse aggregate, 0.075-3mm fine aggregate, mineral powder and matrix asphalt, without fiber admixture, wherein the asphalt content is 6.0wt.%, the coarse aggregate content is 40%, the fine aggregate content is 53%, the mineral powder content is 7%, and the nominal maximum particle size of the asphalt mixture is 9.5mm.
[0062] Comparative Example 2
[0063] A common hot-mix asphalt mixture is composed of 3-10 mm coarse aggregate, 0.075-3 mm fine aggregate, mineral powder and matrix asphalt, with only Kevlar aramid fiber added, wherein the asphalt content is 6.0wt.%, the coarse aggregate content is 40%, the fine aggregate content is 53%, the mineral powder content is 7%, the Kevlar aramid fiber content is 0.05%, and the nominal maximum particle size of the asphalt mixture is 9.5 mm.
[0064] Comparative Example 3
[0065] A common hot-mix asphalt mixture, which consists of 3-20 mm coarse aggregate, 0.075-3 mm fine aggregate, mineral powder and matrix asphalt, without fiber admixture, wherein the asphalt content is 5.8 wt.%, the coarse aggregate content is 59%, the fine aggregate content is 36%, the mineral powder content is 5%, and the nominal maximum particle size of the asphalt mixture is 19 mm.
[0066] Comparative Example 4
[0067] A common hot-mix asphalt mixture is composed of 3-20 mm coarse aggregate, 0.075-3 mm fine aggregate, mineral powder and matrix asphalt, and only Kevlar aramid fiber is added. The asphalt content is 5.8wt.%, the coarse aggregate content is 59%, the fine aggregate content is 36%, the mineral powder content is 5%, the Kevlar aramid fiber content is 0.05%, and the nominal maximum particle size of the asphalt mixture is 19 mm.
[0068] In addition, the inventors found during the research that the dispersibility of Kevlar fiber is closely related to the performance of its asphalt mixture. Since polyethylene fiber will melt during the mixing process, there is no dispersion problem. Therefore, the effect of the addition of polyethylene fiber on the performance of asphalt mixture is not significant.
[0069] The asphalt mixture specimens prepared in the above Examples 1-7 and Comparative Examples 1-4 were tested for road performance, and the specific test method is as follows:
[0070] 1) Centrifugal fiber extraction test:
[0071] The mixed loose asphalt mixture was placed in a centrifugal separator, and trichloroethylene solution (700 mL) was used to dissolve the asphalt, leaving only aggregates and fibers. Kevlar aramid fibers were then extracted, and the Kevlar aramid fibers in different states were cleaned, dried and weighed, and the fiber dispersion rate was calculated.
[0072] 2) Hamburger rutting test:
[0073] Asphalt mixture specimens will be prepared Preheat the oven to 50°C, then apply a constant pressure of 700N and test for 20,000 cycles until obvious rutting occurs on the specimen. Record the rutting depth after each cycle.
[0074] 3) Fatigue test:
[0075] Asphalt mixture specimens Place it in the environmental chamber for at least 90 minutes. First, perform a dynamic modulus test to obtain the initial modulus value of the material. Then, according to the initial modulus value, select the test strain level of different specimens. Start the cyclic fatigue test at 10Hz and 18℃. Based on the viscoelastic damage mechanics theory, use the cracking index S app The cracking characteristics are evaluated by S app The larger the value, the better the anti-fatigue properties.
[0076] 4) Long-term aging test:
[0077] The loose asphalt mixture was subjected to a long-term aging test at 95°C for 4 days, and then the molded specimens were subjected to fatigue tests to test their fatigue cracking characteristics.
[0078] Examples 1-5 and Comparative Examples 1-2 are polyethylene / aramid composite fiber asphalt mixture with a nominal maximum particle size of 9.5 mm, ordinary hot mix asphalt mixture and aramid fiber asphalt mixture, respectively. The test results are shown in Table 2.
[0079] Table 2 Test results
[0080]
[0081]
[0082] It can be seen from the test data in Table 2 that: comparing Comparative Examples 1-2 and Examples 1-5, the anti-rutting performance, fatigue cracking characteristics and cracking performance after aging of Examples 1-5 are all better than those of Comparative Example 1 without fiber addition and Comparative Example 2 with single aramid fiber addition, indicating that the co-addition of Kevlar aramid fiber and ultra-high molecular weight polyethylene fiber not only improves the fatigue cracking and high temperature rutting characteristics of the asphalt mixture, but also improves the anti-aging cracking of the asphalt mixture, and the performance improvement of Example 5 is the most obvious, and its fiber dispersion is the highest, which is significantly higher than that of the implementation case 1 of the traditional mixing method. In summary, the coarse aggregate layered mixing method and the co-addition of Kevlar aramid fiber and ultra-high molecular weight polyethylene fiber can improve the dispersion of Kevlar aramid fiber and improve the mechanical properties of SUP-9.5 asphalt mixture, thereby extending the service life of the asphalt pavement.
[0083] Examples 6-7 and Comparative Examples 3-4 are polyethylene / aramid composite fiber asphalt mixture with a nominal maximum particle size of 19 mm, ordinary hot mix asphalt mixture and aramid fiber asphalt mixture, respectively. The test results are shown in Table 3.
[0084] Table 3 Test results
[0085]
[0086] It can be seen from the test data in Table 3 that: comparing Comparative Examples 3-4 and Examples 6-7, the anti-rutting performance, fatigue cracking characteristics, and cracking after aging of Examples 6-7 are all better than those of Comparative Example 3 without fiber addition and Comparative Example 4 with single aramid fiber addition, indicating that the co-addition of Kevlar aramid fiber and ultra-high molecular weight polyethylene fiber not only improves the fatigue cracking and high-temperature rutting characteristics of the asphalt mixture, but also improves the anti-aging cracking characteristics of the asphalt mixture, and the performance improvement of Example 7 is the most obvious, and its fiber dispersion and mechanical properties are higher than those of Example 6 using the traditional mixing method. It can be seen that in the process of mixing SUP-19 asphalt mixture, the coarse aggregate layered mixing method is adopted, and the co-addition of Kevlar aramid fiber and ultra-high molecular weight polyethylene fiber can also improve the dispersion of Kevlar aramid fiber, and enhance the mechanical properties of SUP-19 asphalt mixture, thereby improving the fatigue life of its pavement.
[0087] It can be seen from the test data that the addition of Kevlar aramid fiber and ultra-high molecular weight polyethylene fiber into asphalt mixture and the improvement of mixing process can improve the dispersion of Kevlar aramid fiber in asphalt mixture, and improve the high-temperature rutting properties, fatigue cracking resistance and aging cracking resistance of asphalt mixture, which is beneficial to extend the service life of asphalt pavement and promote the application of Kevlar aramid fiber in asphalt mixture.
[0088] The embodiments of the present invention are only examples. Although the specific details are described, they do not limit the protection scope of the invention. Those skilled in the art may make various modifications and optimizations to the invention without departing from the core idea of the invention, which are all included in the protection scope of the present invention. Therefore, the final protection scope should be determined according to the attached claims.
Claims
1. A polyethylene / aramid composite fiber asphalt mixture, characterized in that: The raw material composition is as follows by weight percentage: 5.8%-6.0% asphalt, 0.05%-0.1% polyethylene / aramid fiber, 40%-59% coarse aggregate, 36%-53% fine aggregate and 5%-7% mineral powder.
2. The polyethylene / aramid composite fiber asphalt mixture according to claim 1, characterized in that: The polyethylene / aramid composite fiber asphalt mixture is an asphalt concrete mixture, and the nominal maximum particle size is 9.5 mm-19 mm.
3. The polyethylene / aramid composite fiber asphalt mixture according to claim 1, characterized in that: The lengths of the polyethylene fiber and the aramid fiber are both 15-20 mm, and the mixing mass ratio of the polyethylene fiber to the aramid fiber is (1-5):1; Preferably, the lengths of the polyethylene fiber and the aramid fiber are both 19 mm, and the mixing mass ratio of the polyethylene fiber to the aramid fiber is 4:
1.
4. The polyethylene / aramid composite fiber asphalt mixture according to claim 1, characterized in that: The coarse aggregate is crushed stone with a particle size of 3-20 mm, and the fine aggregate is crushed stone with a particle size of 0.075-3 mm.
5. The polyethylene / aramid composite fiber asphalt mixture according to claim 1, characterized in that: The mineral powder is limestone mineral powder and slag powder. Or, the asphalt is base asphalt; Or, the polyethylene fiber is an ultra-high molecular weight polyethylene fiber, and the molecular weight of the polyethylene fiber is 3-4 million; Or, the aramid fiber is Kevlar aramid fiber.
6. A method for preparing the polyethylene / aramid composite fiber asphalt mixture according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Preheat the coarse aggregate, fine aggregate, asphalt and mixing tools separately; (2) First, mix the coarse aggregate with aramid fiber, then add asphalt and polyethylene fiber, and finally add fine aggregate and mineral powder.
7. The method for preparing the polyethylene / aramid composite fiber asphalt mixture according to claim 6, characterized in that: In step (1), the preheating temperature of the coarse aggregate and the fine aggregate is 160-170°C for 20-30 hours; the preheating temperature of the asphalt is 150-155°C for 1-2 hours; the preheating temperature of the mixing tool is 150-155°C for 1-2 hours; Preferably, the coarse aggregate and the fine aggregate are preheated at a temperature of 165°C for 24 hours; The asphalt is preheated at 155°C for 2 hours; The mixing tool is preheated to 155°C for 2 hours.
8. The method for preparing the polyethylene / aramid composite fiber asphalt mixture according to claim 6, characterized in that: In step (2), the mixing process is as follows: the aramid fiber and the preheated coarse aggregate are divided into multiple portions, one portion of the coarse aggregate is mixed with one portion of the aramid fiber to obtain a first mixture; another portion of the coarse aggregate is added to the first mixture and mixed, and the remaining aramid fiber is added to mix to obtain a second mixture; the remaining coarse aggregate is added to the second mixture and mixed, asphalt and polyethylene fiber are added to mix, and finally fine aggregate and mineral powder are added to mix; Preferably, the aramid fiber is divided into 2 equal parts, and the preheated coarse aggregate is divided into 3 parts; first, 1 / 3 of the coarse aggregate is mixed with 1 / 2 of the aramid fiber to obtain a first mixture; then 1 / 3 of the coarse aggregate is added to the first mixture and mixed, and the remaining 1 / 2 of the aramid fiber is added to mix to obtain a second mixture; the remaining 1 / 3 of the coarse aggregate is added to the second mixture and mixed, asphalt and polyethylene fiber are added to mix, and finally fine aggregate and mineral powder are added to mix.
9. The method for preparing polyethylene / aramid composite fiber asphalt mixture according to claim 6, characterized in that: In step (2), the mixing time of the asphalt and the polyethylene fiber is 180-200 seconds; The mixing time of the fine aggregate and the mineral powder is 100-120s; Preferably, the mixing time of the asphalt and the polyethylene fiber is 180s; The mixing time of the fine aggregate and mineral powder is 120s.
10. Use of the polyethylene / aramid composite fiber asphalt mixture according to any one of claims 1 to 5 in asphalt road construction.
Citation Information
Cited By
Pretreatment device for improving dispersity of synthetic fibers in asphalt mixture
CN119932992A
A pretreatment device for improving the dispersibility of synthetic fibers in asphalt mixtures
CN119932992B